2004
DOI: 10.1097/01.ju.0000129228.92805.31
|View full text |Cite
|
Sign up to set email alerts
|

Does the Endoscopic Technique of Ureterocele Incision Matter?

Abstract: Although our results are similar to those of other methods, percutaneously assisted cystoscopic incision of ureterocele enables easier and more accurate decompression. However, when comparing the various techniques described, it seems that postoperative results mostly reflect the anatomical and functional characteristics of the urinary system rather than the technique used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 17 publications
1
12
0
4
Order By: Relevance
“…Endoscopic decompression of the ureterocelic sac and of upper tract dilatation included several modalities, that have been offered along the last two decades: unroofing, incision, and punctures are different methods proposed and adopted to decompress the UTC (2022). The energy source used for decompression includes Collins knife, diathermic electrocautery, and more recently holmium laser (14, 22).…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic decompression of the ureterocelic sac and of upper tract dilatation included several modalities, that have been offered along the last two decades: unroofing, incision, and punctures are different methods proposed and adopted to decompress the UTC (2022). The energy source used for decompression includes Collins knife, diathermic electrocautery, and more recently holmium laser (14, 22).…”
Section: Discussionmentioning
confidence: 99%
“…We think that technical factors may interfere in the outcomes of TUI in DSU. It has been reported that the choice of TUI approach is important for achieving efficient decompression without causing VUR [23] , [24] . Whatever the approach, it is recommended that the TUI should be performed above the level of the bladder wall in the intravesical portion of the ureterocoele to create a valve-like flap, thus avoiding VUR [15] , [19] , [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the occurrence of de novo reflux and the decompression rate of the upper urinary system, there is no significant difference among the methods of endoscopic ablation (Table 3). 50–55 Further randomized controlled studies are necessary for such an alternative approach.…”
Section: Introductionmentioning
confidence: 99%